2021
DOI: 10.1097/jxx.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting nurse practitioners' integration of evidence into practice

Abstract: Background: Evidence-based clinical practice guidelines bridge the gap between clinical practice and research, improve patient outcomes, promote consistency of care, and enhance quality of care. However, guideline adherence varies widely among individual providers and organizations. Purpose: To identify factors that facilitate or impede nurse practitioners' integration of guideline recommendations into practice. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
4
0
6
Order By: Relevance
“…APNs believed that EBP positively affected patient outcomes (Alshammari et al., 2021; Bhatarasakoon et al., 2022; Butler, 2011; Campbell, 2012; Gerrish et al., 2011: Hamilton et al., 2022; Harper et al., 2017; Malik et al., 2015; Van Roper, 2011) and led to the best clinical care (Butler, 2011; Campbell, 2012; Gerrish et al., 2011; Hamilton et al., 2022; Harper et al., 2017; Profetto‐McGrath et al., 2010). They felt that evidence‐based practice is fundamental to professional practice (Bhatarasakoon et al., 2022; Hamilton et al., 2022). One of their strongest EBP competencies was questioning clinical practice (Harper et al., 2017) but they rarely used evidence to make or develop research proposals (Campbell, 2012; Profetto‐McGrath et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…APNs believed that EBP positively affected patient outcomes (Alshammari et al., 2021; Bhatarasakoon et al., 2022; Butler, 2011; Campbell, 2012; Gerrish et al., 2011: Hamilton et al., 2022; Harper et al., 2017; Malik et al., 2015; Van Roper, 2011) and led to the best clinical care (Butler, 2011; Campbell, 2012; Gerrish et al., 2011; Hamilton et al., 2022; Harper et al., 2017; Profetto‐McGrath et al., 2010). They felt that evidence‐based practice is fundamental to professional practice (Bhatarasakoon et al., 2022; Hamilton et al., 2022). One of their strongest EBP competencies was questioning clinical practice (Harper et al., 2017) but they rarely used evidence to make or develop research proposals (Campbell, 2012; Profetto‐McGrath et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Inspection of the background data showed that although the reviewed studies focused on APNs, who in principle must hold at least a master's degree, there were only three studies in which all participants had this level of education (Butler, 2011; Hamilton et al., 2022; Woo et al., 2019). The levels of education in the other studied populations were variable and, in some cases, extremely low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participant is then asked to access a web-based survey via a QR code. Hamilton et al (2022) sent postcards to a list of 5,242 NPs in Alabama to yield a sample of 150 participants (response rate of 2.86%), and DeClerk et al (2022) sent 2,566 postcards to NPs in Arkansas to yield a sample of 277 participants (10.8%). Both examples have a large participant pool and reasonable sample size, yet low response rates.…”
Section: Discussionmentioning
confidence: 99%
“…Investigaciones hasta 2020 contextualizan las barreras en cinco contextos: Político-Social, Organizacional, profesional (41,42,43,44,45,46) y en el contexto del paciente, (42,43,44,47,48) y en el contexto de las directrices de las guías. (41,42,43,44,45,46) Desde la perspectiva de enfermería, estas barreras plantean obstáculos significativos que afectan directamente la capacidad de los profesionales de la salud para brindar una atención basada en la evidencia y centrada en el paciente.…”
Section: Barreras Para La Implementaciónunclassified